2013
DOI: 10.1002/cne.23293
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical distribution of calretinin and calbindin (D‐28k) in the brain of the cladistian Polypterus senegalus

Abstract: Polypteriform fishes are believed to be basal to other living ray-finned bony fishes, and they may be useful for providing information of the neural organization that existed in the brain of the earliest ray-finned fishes. The calcium-binding proteins calretinin (CR) and calbindin-D28k (CB) have been widely used to characterize neuronal populations in vertebrate brains. Here, the distribution of the immunoreactivity against CR and CB was investigated in the olfactory organ and brain of Polypterus senegalus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(59 citation statements)
references
References 140 publications
(246 reference statements)
12
47
0
Order By: Relevance
“…The antiserum has previously been used in several nonmammalian species, including different fishes and amphibians, and it has shown no cross-reaction with other monoamines [Stuesse and Cruce, 1992;Marín et al, 1998;Adrio et al, 1999;Antri et al, 2006;Abalo et al, 2007;Carrera et al, 2008;López et al, 2009;. The specificity of ChAT, CB, and CR antisera has been previously described in Polypterus [Graña et al, 2013;, and the distribution patterns for these markers are similar in the brain of Erpetoichthys (present results).…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…The antiserum has previously been used in several nonmammalian species, including different fishes and amphibians, and it has shown no cross-reaction with other monoamines [Stuesse and Cruce, 1992;Marín et al, 1998;Adrio et al, 1999;Antri et al, 2006;Abalo et al, 2007;Carrera et al, 2008;López et al, 2009;. The specificity of ChAT, CB, and CR antisera has been previously described in Polypterus [Graña et al, 2013;, and the distribution patterns for these markers are similar in the brain of Erpetoichthys (present results).…”
mentioning
confidence: 61%
“…1 h, 4 e). A remarkable population of CBcontaining cells has been observed in the PVO, described within the dorsal and caudal hypothalamic parts [Graña et al, 2013] with CSF-contacting processes, and we observed that they intermingled with the serotonergic cells, but no double-labeled cells were detected.…”
Section: Forebrainmentioning
confidence: 71%
See 3 more Smart Citations